Profil Perencanaan Karier Siswa SMA Athirah 1 Makassar - Ashshafwan, Abdul Wahid; Masnawati, Masnawati; Latif, Suciani (Indonesian Journal of School Counseling: Theory, Application, and Development, 2025)
This study aimed to examine the career planning profile of eleventh-grade students at SMA Islam Athirah 1 Makassar based on five key dimensions: self-concept awareness, career planning orientation, career exploration activities, knowledge of the world of work, and career decision-making readiness. Employing a quantitative survey method, data were collected from 106 students using a standardized career planning scale and analyzed through descriptive statistics and Independent Sample t-Test. The results showed that the students’ overall career planning was at a moderately good level (M = 4.00 on a 1–5 scale), with the highest score in career decision-making readiness (M = 4.15) and lower scores in career exploration (M = 3.82) and work-related knowledge (M = 3.87). No significant gender differences were found across all dimensions (p > 0.05). These findings suggest the need to enhance school-based career guidance programs, especially in facilitating exploration and improving access to occupational information